Design, implementation and characterization of an Optical Coherent Tomography system based on a swept infrared laser source for the structural and biomechanical measurement of ocular and skin tissues - Valencia Rivera, Roger Agustin (2025)
This work was funded by CONCYTEC through the PROCIENCIA program under the competition E041-2023-02 "Applied Research Projects 2023-02", according to the contract PE501082168- 2023 "Development of the first coherent optical tomography system with elastography in Peru for the early detection of Keratoconus and other ocular diseases"